Position tracking of automatic rack and pinion steering linkage system through hardware in the loop testing - Mohammad Nasir, Mohd Zakaria; Dwijotomo, Abdurahman; Abdullah, Mohd Azman; Hassan, Muhammad Zahir (2012)
VehicIe handling behavior is much influenced by the performance of steering system and its mechanism. Steering linkage play a very important role in maneuvering of a vehicle. In this paper, a set of kinematic relations of rack and pinion steering linkage system are modeled in MATLAB SIMULINK environment based on kinematic model equations is presented in study tile relationship between steering wheel angle and tire angle. A Hardware-in-the-loop simulations (HILS) test rig with actual rack and pinion mechanism has been set up using XPC TARGET environment, LVDT and encoder sensors installed for data measurement at various steering angle. Results from simuIation model demonstrate a linear pattern occurred from maximum lock-to-lock steering wheel angle and it is closely follow the sine input trend through HILS experiment with acceptable error.